Pengaruh Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Oleh Guru PAK Terhadap Berpikir Kritis Siswa Kelas Fase E SMA Negeri 1 Tinada - Sitompul, Sabar Rudi; Bancin, Wesli Edrianto; Widiastuti, Maria (Institut Agama Kristen Negeri Tarutung, 2025)
This research aims to determine whether there is a positive and significant influence of the Student Teams Achievement Division (STAD) cooperative learning model by PAK teachers on critical thinking of students in Phase E class of SMA N 1 Tinada, Pakpak Bharat Regency, North Sumatra, Academic Year 2024/2025. The research hypothesis is that there is a significant positive influence between the STAD cooperative learning model and critical thinking of students in Phase E class of SMA N 1 Tinada, Academic Year 2024/2025. This research uses a quantitative method with inferential statistical type. The population consists of all students in Phase E class of SMA Negeri 1 Tinada who are Protestant Christians, totaling 62 people. The sampling technique is the entire population of Phase E class students, totaling 62 people. The research instrument is a questionnaire. The results of data analysis show: a) rcount = 0.433 rtable = 0.244 and tcount = 3.720 ttable = 2.000 indicate a positive and significant relationship between the STAD cooperative learning model and critical thinking of students in Phase E class of SMA Negeri 1 Tinada, Academic Year 2024/2025. b) Regression equation Ŷ = 28.082 + 0.4843X. c) Determination test shows the magnitude of the influence is 18.74%. d) Hypothesis test shows Fcount = 13.917 Ftable = 3.15, so H0 is rejected and Ha is accepted. The research concludes that there is a positive and significant influence between the STAD cooperative learning model and critical thinking of students in Phase E class of SMA Negeri 1 Tinada, Academic Year 2024/2025.